Effects of Steaming and Air‐Drying on Ginsenoside Composition of Korean Ginseng (Panax ginseng C.A. Meyer). Issue 2 (26th November 2014) - Koh, Eunmi; Jang, Ok‐Hee; Hwang, Kyu‐Hyon; An, Young‐Nam; Moon, BoKyung
Abstract This study aimed to compare the ginsenosides composition of ginseng depending on cultivated region and processing method. Fresh ginseng roots collected from four major regions of Korea were processed using either air‐drying or steaming, and subsequent air‐drying. Five ginsenosides including Rg1, Re, Rb1, Rc and Rb2 were the major forms in fresh ginseng, whereas Rb1 and Rg1 were abundant in processed ginsengs. The contents of total ginsenoside decreased with thermal processing and also showed a regional difference between processed ginsengs, whereas fresh ginseng had a regional variation only in Rg1. Unlike another ginsenosides decreased by processing, Rb1 increased with thermal processing. Ginsengs with relatively much higher content of Rc in fresh ginseng had a significant loss by air‐drying and had about five times higher content of Rg3 than that of fresh ginseng. This indicates that Rc was transformed into Rg3 during air‐drying. Practical Applications Korean ginseng used as a traditional medicine because of various beneficial effects is thermally processed to improve its efficacy. Ginsenoside is an interesting bioactive compound found in ginseng. Processing methods, air‐drying or steaming, and subsequent air‐drying, changed ginsenosides qualitatively and quantitatively. These results suggest that processing conditions should be carefully employed to enhance or retain the pharmaceutical effects of ginseng products.